Analisis Strategi Pengembangan pada Aspek Manajemen Industri Halal dalam Perspektif Ekonomi Islam - Muhammad Fatkhul Arifin; Abdur Rahman (Al Rikaz: Jurnal Ekonomi Syariah, 2023)
This research aims to determine the strategy analysis for developing management aspects in the halal industry and analysis of the halal industry from an Islamic economic perspective. This research is qualitative in nature with a literature review method from secondary data such as books, journals and available previous research. Descriptive analysis techniques are used to examine data in depth and systematically, thereby producing accurate and up-to-date information. The findings from this research show that management in the halal industry includes human resource development, socialization of halal certification, development of a halal ecosystem, involvement of various parties in certification, as well as international cooperation to guarantee halal products. External challenges include global competition and varying halal certification standards, while internal challenges include low halal awareness and slow implementation of regulations. The Islamic economic perspective emphasizes that halal industry must be based on sharia principles, with the aim of achieving prosperity in this world and the hereafter. With effective management and the right development strategy, the halal industry has great potential to develop and contribute significantly to the national economy.